Chaos in the Sporting World over Russia's War of Aggression: Political Neutrality in Light of Human Rights Protection - Wiater-Hellgardt, Patricia (Business and Human Rights Journal, 2023)
There is currently disagreement in the international sports world about whether Russian and Belarusian athletes should be admitted to international competitions. While initially proposing to ban these athletes, the International Olympic Committee (IOC) is now recommending that sports federations readmit Russian and Belarusian athletes under certain conditions. The IOC believes that this is unavoidable in order to respect human rights. Sports federations are invoking their autonomy on this issue, with some following the IOC's advice, some maintaining a ban, and others allowing unconditional participation. This piece seeks to correct the IOC's interpretation of the applicable human rights standard. It asserts that sporting bodies must respect human rights, and that the principles of autonomy and neutrality of sport must be considered in light of internationally recognised human rights standards. If these are used as a yardstick, it becomes clear that collective exclusion can be justified in the extreme case of a war of aggression.
CRIS-Team Scopus Importer:2023-09-29
Keywords: discrimination; international sports federations; political neutrality; proportionality; Russia's war of aggression

Fundamental Rights of Corporations as International Human Rights: The Perspective of Regional Economic Courts - Wiater-Hellgardt, Patricia (Human Rights Law Review, 2023)
The article deals with the question of whether and why international human rights law should protect corporations at the example of regional economic integration systems such as the European Union. For the European Court of Justice, granting human rights to corporations is the natural response to the key role that private companies play in the integration program. Regional human rights courts, in contrast, partly struggle to recognise corporations as human rights holders. The article critically examines the theoretical raison d’être of fundamental rights of corporations, granted in the framework of international human rights, and reflects on them on the basis of a Rule of Law-postulate.
CRIS-Team Scopus Importer:2023-11-24
Keywords: European Union; fundamental rights; K E Y W O R D S: corporations; regional economic integration; regional human rights protection; Rule of Law

On the notion of "Partnership" in critical infrastructure protection - Wiater, Patricia (European Journal of Risk Regulation, 2015)
This article is a critical reflection on the manifoldness of the notion of "partnership" in Critical Infrastructure Protection. It is argued that the partnership arrangement can be a promising political approach to CIP if the details of public-private cooperation - that is: the participants, the duration, the responsibilities and duties, as well as possible financial compensation - are formalized. Illusionary ideas of a "partner-like" relationship between the public and the private, such as those laid down in the German "National Strategy for Critical Infrastructure Protection", are, however, doomed to fail. State authorities have to actively offer binding regulatory arrangements to private CI firms in order to establish which companies genuinely agree to cooperate - and which do not. Due to the state's constitutional obligation to guarantee national security and protect the life and health of its citizens, introducing legal requirements is the only possible reaction to a company's refusal to cooperate. In order to avoid overly intrusive market intervention, the state's offer to private firms or their industry associations to conclude binding regulatory contracts on CIP matters may serve as a promising compromise between a laissez-faire approach and regulation.
CRIS-Team Scopus Importer:2023-03-21

Rights of Action of Business Entities in Regional Economic Systems - Wiater-Hellgardt, Patricia (European Yearbook of International Economic Law 2020, 2022)
Direct and state-independent rights of action of private business entities are still exceptional in international economic law and are limited to a small number of regional economic systems. Based on the examples of the European Union (EU), the European Economic Area (EEA), the East African Community (EAC), the Southern African Development Community (SADC), the Economic Community of West African States (ECOWAS) and the Caribbean Community (CARICOM), this article examines the status quo of the procedural empowerment of business entities on regional integration levels. It reveals that both the contracting states and the regional economic courts engaged in interpreting individual rights of action attribute different functions to the role of business entities as litigants: Understood as instruments of economic and legal participation and control, individual rights of action give companies the opportunity to actively contribute to shaping the effectiveness of law enforcement in the integration process by means of court proceedings. This functional understanding has to be complemented by a rule of law approach. In this approach, states and courts perceive business entities’ rights of action to the regional courts primarily as defensive instruments, guaranteeing freedom from burdensome state or Community law interventions in the legal or economic positions of a company. The understanding as defensive instruments prevails (with the exception of the historical European Court of Justice (ECJ) in interpreting the Treaty establishing the European Coal and Steel Community (ECSC Treaty)) in the European systems of individual legal protection and, in some regards, in the ECOWAS legal system. By contrast, a functional understanding can be found in the rest of the African systems and in the Caribbean Community.
CRIS-Team Scopus Importer:2022-12-09